После преобразования правой части какое выражение получим?


После преобразования правой части какое выражение получим?

alelinahka alelinahka    2   10.09.2021 21:10    0

Ответы
AdinaKhamzina1 AdinaKhamzina1  10.09.2021 22:00

Объяснение:

  1        t^2-g^2        4

 *   -  ---  =

 t+g       gt               t

  1      ( t-g)*(t+g)    4

*    -  =

t+g         gt            t

  t-g       4      t-g-4g     t-5g

   - =  = ;

  gt         t          gt          gt

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра